Parasomnia, volume 2 ebook The dreaming god. - Bunn, Cullen (Parasomnia, 2023)
Cullen Bunn (Harrow County) and Andrea Mutti (Bunny Mask) return with their hit adventure tale of two worlds split between dreams and reality.As the hunt for his missing son continues, our hero shifts worlds from the nightmarish Lovecraftian dreamscape to a cyberpunk metropolis where a ruthless cult continues to plague him, and reality and fantasy continue to blur.Collects Parasomnia: The Dreaming God #1–#4.